Valhellions - Akers, Tim, 1972- (Akers, Tim, 1972- Knight watch, 2023)
"An agent of Knight Watch, tasked to protect humanity from supernatural enemies, must go to hell and back to clear his name and save the world. When John Rast signed up for Knight Watch, he expected it to be all fighting dragons and rescuing maidens. You know, hero stuff. But instead he's stuck patrolling game conventions and cosplayer competitions, looking for dangerous anachronisms and the villains who may be trying to exploit them. Fortunately, all that changes when an honest-to-goodness necromancer shows up wielding a weapon created by Nazi occultists and accompanied by some badass evil Valkyries, hell-bent on kicking off the end of the world. John and the team will go to great lengths-even Minnesota-to prove find out who's responsible for all this and foil their plans. Also, there's a giant dog who thinks the moon is a ball. It's epic"--